2014
DOI: 10.1186/1472-6882-14-172
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the antibiotic potential of essential oils against Haemophilus ducreyi

Abstract: BackgroundHaemophilus ducreyi is the bacterium responsible for the genital ulcer disease chancroid, a cofactor for the transmission of HIV, and it is resistant to many antibiotics. With the goal of exploring possible alternative treatments, we tested essential oils (EOs) for their efficacy as antimicrobial agents against H. ducreyi.MethodsWe determine the minimum inhibitory concentration (MIC) of Cinnamomum verum (cinnamon), Eugenia caryophyllus (clove) and Thymus satureioides (thyme) oil against 9 strains of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
1
4
0
1
Order By: Relevance
“…The MIC values for the antibiotics against both bacteria were within the range as previously reported in the literature [i.e., 0.06-0.5 μg/mL for doxycycline (Goldstein et al, 2012) and ≤16 μg/mL for tilmicosin (McClary et al, 2011)]. Essential oils are often indicated as alternatives to synthetic antibiotics, due to their antimicrobial activity, as well as low risks of side effects or bacterial resistance (Lindeman et al, 2014). However, such application only becomes true if these compounds are used at high concentrations as feed (Melo et al, 2015) or food additives (Wu et al, 2015), or topically administered (Lindeman et al, 2014).…”
Section: Short Communicationsupporting
confidence: 75%
“…The MIC values for the antibiotics against both bacteria were within the range as previously reported in the literature [i.e., 0.06-0.5 μg/mL for doxycycline (Goldstein et al, 2012) and ≤16 μg/mL for tilmicosin (McClary et al, 2011)]. Essential oils are often indicated as alternatives to synthetic antibiotics, due to their antimicrobial activity, as well as low risks of side effects or bacterial resistance (Lindeman et al, 2014). However, such application only becomes true if these compounds are used at high concentrations as feed (Melo et al, 2015) or food additives (Wu et al, 2015), or topically administered (Lindeman et al, 2014).…”
Section: Short Communicationsupporting
confidence: 75%
“…The bud EO exhibited MICs of 50, 100 and 400 μg/mL against Haemophilus ducreyi , S. aureus and E. coli , respectively. Leaf EO demonstrated MICs of 250–500 μg/mL against dental pathogens such as Fusobacterium nucleatum, Porphyromonas gingivalis and Streptococcus mitis ( Bersan et al, 2014 ; Lindeman et al, 2014 ; Thielmann et al, 2019 ). Eugenol ( 27 ), a phenolic compound, is the main EO constituent with a concentration ranging from 47.64 to 88.58% ( Chaieb et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the fact that starting from the 1970s, some strains of H. ducreyi have shown resistance to penicillin and its derivatives and then to sulfonamides, aminoglycosides, tetracyclines, and chloramphenicol it is of particular concern the search of new compounds given the connection between Human Immunodeficiency Virus 1 (HIV-1) and chancroid. The authors showed the antibacterial activity, expressed as MIC and minimum lethal concentrations, of the essential oil obtained from C. verum [ 61 ].…”
Section: Antibacterial Effects Of Cinnamon Essential Oil and Cinnamentioning
confidence: 99%